Minimalisasi Kekurangan Material melalui Implementasi Quality Control Circle - Togar W. S. Panjaitan; Debora A. Y. A.; Marissa Yessicha (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2011)
The revolution of traditional quality management concept into total quality management (TQM) inspired industry for establishing and implementing quality control circle (QCC). Before starting a project as the implementation of the QCC, the training was held for supporting the knowledge of the QCC team. As the pilot project of the QCC, this research will try to minimize the percentage of the lack material in the production process of 8340 type by working together with the QCC team. The result of QCC implementation could reach the target set by the team, the percentage of the lack material reached less than 3%. The percentage of the lack material kontaktarm reduced from 3.09% to 0.00%, flachdrahtspule reduced from 9.20% to 0.40%, and niet reduced from 7.71% to 2.73%. Besides, the implementation of QCC also resulted in positive impact for all the members of the team about the benefits and experiences gained.